THE USE OF INDIRECT CORRECTIVE FEEDBACK IN MONITORING STUDENTS’ WRITING ACCURACY - Rika Rahmawati Suryana; Reni Apriani (English Didactic, 2020)
AbstractThis research aimed to explore the use of Indirect Corrective Feedback (ICF) in monitoring students’ writing accuracy, the students’ attitudes toward Indirect Corrective Feedback, and the benefits of Indirect Corrective Feedback. This was a  qualitative research which used a case study method. This research was conducted at SMAN 3 Rangkasbitung. It involved only one class is the students of X MIPA 3 in SMAN 3 Rangkasbitung. This class consists of 36 students but in this research the writer focus on 10 students. The writer choosen it purposively. the writer answered the research questions by using four instruments such as document, questionnaire, interview, and observation. Then results of this research revealed that first, ICF could improve students` writing accuracy. Second, ICF helps the students to write better. Third, ICF help the student to avoid the same errors. Fourth, ICF makes the students more independent, and ICF motivates students to learn the next writing lesson.